Intervention framework for quality and assurance in information systems projects - El Desouki, Hassan Mohamed Said (Curtin University, 2012)
This study created an intervention framework that could be used to reduce the risk of failure in information technology projects. The study investigated social, cultural, technical and economic issues that affect information technology projects and their ability to achieve positive outcomes. As information technology continues integrating deeper into our life, its complexity and challenges increase and overall project delivery remains challenged.Software development and project management methodologies focus on processes and tools that address technical elements with the intention of ensuring positive project outcomes. However, information technology projects are also affected by social and cultural issues that frequently introduce challenges outside of the scope of traditional methodologies.Since the 1980’s software development and project management methodologies have been widely adopted and competence in the use of these methodologies is often a stated prerequisite for companies and individuals involved in information technology projects. However, project success rates have not improved during this period, despite the prolific use of the project management methodologies.Research published in the area of information technology projects focused on critical success factors, but there is little published on how to actually address issues which cause failure.This research utilised the case study research method covering multiple cases in Australia and South East Asia with the aim of answering the research questions. What are the underlying factors in IT development projects at risk of failure and how can management intervene in a holistic and structured way to address these factors and mitigate the risk of failure? The outcome is a framework for project managers which allows them to overcome challenges that they face during project delivery. The emphasis is on the social and cultural elements, which are frequently unaddressed by traditional project management approaches.The study finds that projects varying in size, geography location, and work environments faced similar challenges. While many employed software development and project management methods, none were able to achieve the stated project objectives.The intervention framework developed in this study is unique and builds upon well-established theories and models. It provides a new approach to social, cultural, technical and economic issues faced by information technology projects and complements existing industry standard software development and project management methodologies. This research informs both project management theory and practice, and indicates that the strengths of the proposed framework can be further elaborated to improve project success and remedy the weaknesses of established methodologies, while increasing the probability of successful delivery of IT projects.